Who creates jobs? Venture capital, research grants, and regional employment in the U.S. Issue 6 (3rd July 2019) - Kang, Hyunsung D.; Edelman, Elazer; Ku, David N.
ABSTRACT: We build on the exploratory and exploitative learning literature that suggests that venture capital and governmental research grants may impact regional employment in a different manner. Using a regional employment dataset in the U.S. (United States) medical device sector, our analysis reveals that research grants contribute to create a greater level of regional employment compared with venture capital funding. Furthermore, the positive effects of both funding sources are more salient when intellectual capital is abundant in the region. More specifically, the interaction effect of research grants and intellectual capital is gradually increased in the long term and eventually becomes greater than that of venture capital and intellectual capital, which is relatively constant. These findings highlight the heterogeneous motivations and consequences of two funding sources that should be considered in the future resource allocation policy accordingly.